2022
DOI: 10.1111/1753-0407.13310
|View full text |Cite
|
Sign up to set email alerts
|

Is metformin a possible treatment for diabetic neuropathy?

Abstract: Metformin is a hypoglycemic drug widely used in the treatment of type 2 diabetes. It has been proven to have analgesic and neuroprotective effects. Metformin can reverse pain in rodents, such as diabetic neuropathic pain, neuropathic pain caused by chemotherapy drugs, inflammatory pain and pain caused by surgical incision. In clinical use, however, metformin is associated with reduced plasma vitamin B12 levels, which can further neuropathy. In rodent diabetes models, metformin plays a neuroprotective and analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Metformin has multiple mechanisms of action, including AMPK activation, inhibition of mitochondrial respiration, increasing insulin sensitivity, and antagonizing the effects of glucagon [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has multiple mechanisms of action, including AMPK activation, inhibition of mitochondrial respiration, increasing insulin sensitivity, and antagonizing the effects of glucagon [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 also enhances cAMP production to facilitate a PKA-induced closure of KATP channels (47). Whether or not metformin or GLP-1 agonists directly or indirectly influences ion channel excitability, and therefore influences incidence of chronic pain, particularly from diabetes is up for debate (66)(67)(68). According to a recent cohort study, patients with diabetes who taking opioids were at increased risk of early mortality compared to diabetic and non-diabetic participants who did not use opiates and non-diabetics using opiates (69).…”
Section: Discussionmentioning
confidence: 99%
“…151 In addition, metformin, an insulin sensitiser widely used in the treatment of NAFLD, IR and type 2 diabetes, has been found to inhibit the absorption of B12. 152 Mahabir S et al found the serum FA in the overweight postmenopausal women was lower than healthy individuals despite the adequate intake of FA. 153 Therefore, the supplementation of FA and B12 in addition to the application of such patient may be beneficial to the NAFLD, and the effect of dietary structure changes or probiotic supplementation may be better than that of oral FA supplementation alone, but needed further verification studies.…”
Section: Conclusion and Future Considerationsmentioning
confidence: 98%
“…In addition, metformin, an insulin sensitiser widely used in the treatment of NAFLD, IR and type 2 diabetes, has been found to inhibit the absorption of B12 152 . Mahabir S et al.…”
Section: Conclusion and Future Considerationsmentioning
confidence: 99%